Temperature Detection and Control Circuit - Chen, Peng (Journal of Theory and Practice of Engineering Science, 2024)
In order to realize energy saving, emission reduction and green development, this design uses one of the basic analog electronic technology and digital electronic technology knowledge to detect the environmental temperature in real time in daily life. If the environmental temperature is lower or higher than the set temperature, it will alarm and regulate. Thermocouple and temperature compensation principle are adopted for temperature sensing in this design; The AD conversion part uses the integrated chip AD574A; The conversion from binary to 8421BCD code is realized by EEPROM 281024; The display decoding part is realized by 74ls48 and digital tube; The temperature control range is set by digital setting, which is realized by 74ls160 decimal plus counter and latch 74ls175; The cascade implementation of the temperature judgment comparison value comparator 74ls85; The multi-channel temperature cycle monitoring function is realized by using 74ls160 and adg508f. Monostable state is added to the audible and visual alarm.